Juridical Analysis of PKPU Decision by The Court on Application for PKPU Revocation by The Debitor - Nandi Pratama; Mohamad Fajri Mekka Putra (Kosmik Hukum, 2023)
The purpose of this study is to find out how the judge's consideration in revoking the Delay of Debt Payment Obligation on the request of the debtor who has been determined to be Debt Payment Suspension, but there are findings of the calculation of the management team of Debt Payment Delay which states that the assets (Activa) of the debtor are still larger. of obligations (liabilites) so as to ask the Court to revoke the Suspension of Debt Payment Obligations. In addition, it is necessary to know how the legal impact that will be received by debtors and creditors on Decision Number: 53/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt.Pst. This study applies a normative juridical research method that makes court decisions as primary legal material and occupies a position after legislation. The primary legal data or materials analyzed in this study are court decisions, namely Decision Number: 53/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt.Pst dated April 12, 2021 and Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. Based on this research, it can be concluded that the application submitted by the debtor in the revocation of the Suspension of Debt Payment Obligations is appropriate because the revocation of the Suspension of Debt Payment Obligations is carried out by the Court based on the provisions stipulated in Article 295 Paragraph (1) of Law Number 37 of 2004 concerning Bankruptcy and Postponement Obligation for Payment of Debt, so that the Central Jakarta District Court has the authority to revoke the Suspension of Obligation for Payment of Debt at the request of the debtor.Keywords: Postponement of Debt Payment Obligations; Revoke PKPU; Bankruptcy; Commercial Court.